'Big Bang' Versus Gradualism in Economic Reforms : An Intertemporal Analysis with an Application to China - Feltenstein, Andrew; Nsouli, Saleh (Washington, D.C. : International Monetary Fund, 2001)
This paper reviews briefly the controversy in the literature concerning the speed of adjustment and sequencing of reforms, and presents a model parameterized with Chinese data. The model is used to generate different policy simulations to illustrate some of the key issues in the debate on the speed and sequencing of reforms, and not to provide a basis for policy recommendations for China. The simulations highlight the importance of the criteria being used for determining speed and sequencing. The paper also underscores the limitations involved in attempting to derive conclusions from the model, given the complexity of the issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet